Selected areas in cryptography - SAC 2015 : 22nd International Conference Sackville, NB, Canada, August 12-14, 2015 revised selected papers /: 22nd International Conference Sackville, NB, Canada, August 12-14, 2015 revised selected papers. (2016) - Unknown
No abstract available